1/x-1/y=3/4

1/x-1/y=3/4

  • frac{1}{x}-frac{1}{y}=frac{3}{4}
xy=2
4(y-x)=3xy
xy=2

4(y-x)=6
y-x=frac{3}{2}
y=1.5+x
x(1.5+x)=2
x^2+1.5x-2=0
D=sqrt{frac{41}{4}}
x_{1}=frac{-1.5-frac{sqrt{41}}{2}}{2}
x_{2}=frac{-1.5+frac{sqrt{41}}{2}}{2}
y_{1}=-frac{8}{sqrt{41}-3}
y_{2}= frac{8}{sqrt{41}+3}
  • Умножим второе на первое
    xy * (1/x -1/y) = 2* 3/4
    y — x = 3/2 =1.5
    y = 1.5+x
    подставим во второе
    x(1.5+x)=2
    1.5x +x^2 = 2
    x^2 +1.5x -2 =0
    умножим на 2
    2x^2 +3x -4 =0
    D = (-3)^2 — 4*2*-4 = 9 +32 = 41
    x1 = 1/4 *(-3 -41)
    x2 = 1/4 *(-3 +41)